The Role of Antioxidant Transcription Factor Nrf2 and Its Activating Compounds in Systemic Lupus Erythematosus - Lu Liu; Karina de Leeuw; Harry van Goor; Johanna Westra (Antioxidants, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease in which kidney involvement, so-called lupus nephritis (LN), is common and one of the most severe manifestations. Oxidative stress (OS) may play a role in the pathogenesis of LN through the exacerbation of inflammation and immune cell dysfunction/dysregulation. Nuclear factor erythroid 2-related factor 2 (Nrf2), also known as nuclear factor erythroid-derived 2-like 2, is a transcription factor that in humans is encoded by the NFE2L2 gene and is regarded as a central regulator of the antioxidative response. Nrf2-activating compounds have been shown to alleviate oxidative stress in cells and tissues of lupus-prone mice. Although the precise mechanisms of Nrf2 activation on the immune system in SLE remain to be elucidated, Nrf2-activating compounds are considered novel therapeutical options to suppress OS and thereby might alleviate disease activity in SLE, especially in LN. This review therefore summarizes the role of the Nrf2 signaling pathway in the pathogenesis of SLE with LN and describes compounds modulating this pathway as potential additional clinical interventions.